2018
DOI: 10.1177/0886260518757227
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the English Language Version of the Violent Ideations Scale

Abstract: This study used a within-participant design to evaluate the concurrent validity and test–retest reliability of the Violent Ideations Scale in a general population, English-speaking opportunistic sample. Data from 116 adult participants ( M age = 33.7, SD = 11.9, male = 30 [25.9%]) were used to compare scores on the Violent Ideations Scale and Aggression Questionnaire and responses to the Schedule of Imagined Violence. A subgroup of 27 participants ( M age = 37.2, SD = 13.6, male = 8 [29.6%]) completed the Viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Factor structure. Previous validation studies examining the VIS showed unidimensionality for the scores of the measure (McKenzie et al, 2021;Murray et al, 2018). Given that the VIS has already been validated in German and English, a confirmatory factor analysis (CFA) was performed to test the scale dimensionality with one-factor solutions with the Spanish sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factor structure. Previous validation studies examining the VIS showed unidimensionality for the scores of the measure (McKenzie et al, 2021;Murray et al, 2018). Given that the VIS has already been validated in German and English, a confirmatory factor analysis (CFA) was performed to test the scale dimensionality with one-factor solutions with the Spanish sample.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the purpose of the study, the items related to psychological aggression were excluded, resulting in a 10-item version. The English version (McKenzie et al, 2021) also provided satisfactory psychometric indicators, test-retest reliability ( r (27) = .769), and internal consistency ( α = .925). As for concurrent validity, the English VIS items significantly correlated with the subscale and total scores of the Aggression Questionnaire (AQ), with r values ranging from .23 (verbal aggression) to .72 (physical aggression).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The VIS showed unidimensionality, minor measurement differences across gender and showed a predictive relation to criminal violence. The scale was also translated and validated in English by McKenzie, et al (2018) in a sample of 116 Englishspeaking adults.…”
Section: Introductionmentioning
confidence: 99%
“…The VIS showed unidimensionality, minor measurement differences across gender and showed a predictive PREPRINT -Validation of an Extended Violent Ideations Scale (The VIS-X) 4 relation to criminal violence. The scale was also translated and validated in English by McKenzie, et al (2018) in a sample of 116 English-speaking adults.…”
Section: Introductionmentioning
confidence: 99%